Chitosan’s Ability to Remove the Smear Layer—A Systematic Review of Ex Vivo Studies - Ana Ferreira-Reguera; Inês Ferreira; Irene Pina-Vaz; Benjamín Martín-Biedma; José Martín-Cruces (Medicina)
Background and Objectives: This systematic review aimed to compare the effect of chitosan in smear layer removal with other commonly used chelators during root canal treatment. Materials and Methods: The PRISMA guidelines were followed. Ex vivo studies performed in non-endodontically treated extracted human permanent teeth with a fully formed apex, in which sodium hypochlorite was the main irrigant and chitosan was used as final irrigation to observe its capacity to remove the smear layer using a Scanning Electron Microscope (SEM), were included. In addition, reviews, letters, opinion articles, conference abstracts, book chapters, or articles that did not use a control group were excluded. A literature search was undertaken without limits on time or language, until February 2024, in PubMed—MEDLINE, Scopus, Web of Science, and in the electronic archives of four endodontic journals. The risk of bias was evaluated by adapting the risk of bias assessment used in a previous study. Study selection, data collection, and synthesis were performed and the risk of bias was assessed by two independent reviewers. Results: Six studies fulfilled the eligibility criteria and were included. Four studies found chitosan to be as effective as EDTA and one paper showed it was more effective than EDTA and MTAD; however, one article found it to be comparable to citric acid. The overall risk of bias was medium. Quantitative analysis of the results was not possible due to the heterogeneity found between the study methodologies of the included articles. Conclusions: Within the limitations of this study, 0.2% chitosan may be considered as a promising irrigation solution when employed as a final irrigant in order to remove the smear layer. Nonetheless, a standardized protocol for the use of chelators in root canal treatment should be established in future studies.